Distal Humeral Fixation of an Intramedullary Nail Periprosthetic Fracture - Hiren M. Divecha; Hans A. J. Marynissen (Case Reports in Orthopedics)
Distal humeral periprosthetic fractures below intramedullary nail devices are complex and challenging to treat, in particular due to the osteopenic/porotic nature of bone found in these patients. Fixation is often difficult to satisfactorily achieve around the intramedullary device, whilst minimising soft tissue disruption. Descriptions of such cases in the current literature are very rare. We present the case of a midshaft humeral fracture treated with a locking compression plate that developed a nonunion, in a 60-year old female. This went on to successful union after exchange for an intramedullary humeral nail. Unfortunately, the patient developed a distal 1/5th humeral periprosthetic fracture, which was then successfully addressed with a single-contoured, extra-articular, distal humeral locking compression plate (Synthes) with unicortical locking screws and cerclage cables proximally around the distal nail tip region. An excellent postoperative range of motion was achieved.